Mental Health of Youth Athletes After Sport Career Termination: A Systematic Review - Knysak, Karol; Maj, Alicja; Piątek, Maja; Jastrzębski, Michał; Hejnosz, Aleksandra; Szczerba, Mateusz; Wilkowska, Krystyna; Kaczorowski , Wojciech; Michałowski, Maciej Karol; Sudomir, Maria; et al. (Quality in Sport, 2026)
Background. Mental health challenges in youth athletes following career termination represent a significant but understudied public health concern. Despite increasing recognition of mental health issues in sports, limited comprehensive evidence exists regarding psychosocial experiences and effective interventions for former youth athletes transitioning out of competitive sport. Aim. To systematically review and synthesize qualitative and quantitative evidence on mental health outcomes and coping mechanisms in youth athletes following sport career termination, identify research gaps, and provide recommendations for clinical practice. Material and methods. A comprehensive systematic literature review was conducted following PRISMA 2020 guidelines. Electronic databases were searched for English-language peer-reviewed articles. Thirteen studies met inclusion criteria (11 qualitative, 2 quantitative). Quality assessment was performed using appropriate tools. Results. The synthesis reveals predominantly qualitative evidence highlighting "social death" and identity foreclosure as primary psychological distress mechanisms. Quantitative data suggest significant psychological distress in the acute post-selection phase and links between high athletic identity and anxiety. However, contrary to deficit narratives, long-term qualitative data indicate high wellness levels and post-traumatic growth facilitated by communal coping and body recalibration. Only two specific interventions (online support groups and Bodies in Motion) were identified. Conclusions. While transition out of sport poses significant risks for psychiatric symptoms driven by identity loss and institutional silence, it offers growth opportunities when supported by holistic interventions. Urgent priorities include developing evidence-based programs addressing somatic "relearning" and leveraging mentorship networks to mitigate isolation.